Diversity and distribution freshwater ichthyofaunal of West Sulawesi. Issue 1 (April 2020) - Nurjirana,; Afrisal, M; Sufardin,; Haris, A; Burhanuddin, A I
Abstract: The diversity of ichthyifauna species is very interesting to study, especially in terms of species inventory as an effort to reveal the biodiversity of aquatic species. Sulawesi is one of the locations in the Wallacea region which is the location with the most species diversity and the location where most of the endemic species found in Indonesia are found. This study purpose to determine the diversity and distribution of ichthyifaunal species in the waters of West Sulawesi, and evaluate the status of conservation based on data from the International Union for Conservation of Nature to determine the level of utilization of species in West Sulawesi. The study was conducted in February 2018 to May 2019, samples were collected from eight rivers from the estuary area to the upper stream of the waters of West Sulawesi. The number of samples that were collected was 771 fish samples consisting of 31 species of fish and from 10 families including, Family Ambassidae, Anguillidae, Gobiidae, Eleotridae, Mugilidae, Gerreidae, Apogonidae, Terapontidae, Lutjanidae, and Leiognathidae. From the total species found, the highest number of species was found from the Gobiidae family, where species from the Gobiidae family dominated at each research station. The conservation status of the fish obtained is in the data deficient status with three species, least concern with 28 species, and near threatened with one species. Distribution of species in the waters of West Sulawesi is spread throughout the Indonesian waters, and some of them are endemic to Sulawesi.